Ritma izjūtas veidošanās 1. klasē mājturībā un tehnoloģijās - Smone, Ināra (Latvijas Universitāte, 2008)
Diplomdarba ‘’ Ritma izjūtas veidošanās 1. klasē mājturībā un tehnoloģijās ” mērķis ir noskaidrot ritma veidošanās iespējas 1. klases skolēniem. Teorētiskajā daļā pētīts ritms kā izteiksmes līdzeklis mājturībā un tehnoloģijās saistībā ar citiem mācību priekšmetiem. Izstrādāts tematiskais plāns ritma izjūtas veicināšanai 1. klasē 16 stundām . Tematiskais plāns aprobēts, analizēti iegūtie rezultāti. Pielikumos aplūkojami vingrinājumu paraugi, intervija, aptauja un bērnu darbu attēli.

The theme of the diploma work is “Formation of the sense of rhythm in Home Economics lessons in class 1”. The aim is to study possibilities of rhythm formation of students in class 1. Theoretical part deals with rhythm as an important means of expression in Home Economics lessons in connection with other subjects. Thematic plan has been worked out to promote and stimulate the sense of rhythm. It is meant for class 1 and contains 16 lessons. The plan is approbated and the results have been analyzed. Exercises, examples, interviews, questionnaires and pictures made by children are discussed in the appendix.
Development of the sense of rhythm in home economics and technologies in Grade 1
Keywords: Pedagoģija